ANALISIS STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN USAHA KOPI KENANGAN DI ERA DIGITAL - Emi Debora Sinaga; Christella Josephine Simbolon; Septy Idola Simamora; Rosianna Hareva Gultom (STKIP Subang, 2026)
The development of information technology has transformed the way companies market their products and services to consumers. The utilization of various digital platforms enables businesses to establish more effective, faster, and broader communication with customers. One company that has successfully adapted to this transformation is Kopi Kenangan, which utilizes social media, digital applications, and online ordering services as part of its marketing strategy. This study aims to examine how the digital marketing strategies implemented by Kopi Kenangan contribute to increasing sales in the digital era.This research employs a qualitative descriptive approach using secondary data obtained from Instagram content analysis, customer reviews on Google Reviews, and information related to the company's outlet network and digital application usage. The findings indicate that Kopi Kenangan's digital marketing activities are primarily focused on building brand awareness through social media content, supported by digital promotions and the convenience of transactions through its mobile application. These strategies have a positive impact on customer experience, enhance customer loyalty, and support sales growth. However, several technical issues related to the digital platform were still identified and require further attention to improve the effectiveness of the company's marketing efforts.